Graphene oxide modified additive for electrolytic copper foil

By introducing oxygen functional groups on graphene and combining other additives to form modified additives, the problem of copper foil performance degradation caused by excessive graphene oxide content is solved, and a high-strength, low-surface roughness lithium-ion battery is prepared. Electrolytic copper foil material achieves excellent mechanical and electrical conductivity of copper foil.

CN119287456APending Publication Date: 2025-01-10江西铜博科技股份有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428827.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, when graphene oxide additive is added to the electrolyte, excessive content will lead to growth and agglomeration, reducing the mechanical properties and conductivity of the copper foil. At the same time, the wetting between graphene and the metal matrix is ​​poor, which affects the The electrodeposition process leads to the performance of copper foil getting better first and then getting worse.

Method used

Graphene oxide modification additive is used to introduce an oxy functional group on the graphene monolithic sheet after oxidation treatment, combining sodium polydisulfide dipropane sulfonate, gelatin, hydrochloric acid, methyl violet, polyethylene glycol and hydroxyethyl fiber. Components such as carbon dioxide form additives in a specific proportion, add to copper sulfate electrolyte, perform electrolytic foil generation, roughening treatment and other processes to prepare electrolytic copper foil material for high strength and extremely thin lithium-ion batteries.

Benefits of technology

It significantly improves the tensile strength and elongation of the copper foil, reduces the surface roughness, avoids the occurrence of pinholes, ensures the excellent mechanical properties and conductivity of the copper foil, and solves the problem of poor mechanical properties of the copper foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287456A_ABST
    Figure CN119287456A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene oxide modified additive for an electrolytic copper foil. The additive is prepared from the following components according to the adding concentration in an electrolyte: 0.2 to 1.0 g / L of graphene oxide, 15 to 20 mg / L of sodium dithiodipropane sulfonate, 1.0 to 2.5 g / L of gelatin, 40 to 50 mg / L of hydrochloric acid, 10 to 18 mg / L of methyl violet, 4.5 to 8 mg / L of polyethylene glycol and 8 to 12 mg / L of hydroxyethyl cellulose. The high-strength ultra-thin electrolytic copper foil material for the lithium ion battery has excellent mechanical properties, does not have obvious pinholes, and can remarkably improve the roughness of the surface of the copper foil. The tensile strength of the prepared copper foil material is larger than 500 MPa, the ductility is larger than 4%, the surface roughness is lower than 300 nm, and through the synergistic effect of specific components, the problem that the mechanical property of the copper foil is poor is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of production and preparation of electrolytic copper foil, and in particular to a graphene oxide modified additive for electrolytic copper foil. Background Art

[0002] Electrolytic copper foil is widely used as negative electrode current collector material for lithium-ion batteries. As various electronic devices develop towards precision, intelligence, and lightness, higher requirements are placed on the overall performance of electrolytic copper foil. [1,2] In order to make the copper foil have better surface morphology and mechanical properties while maintaining good conductivity, the most common method is to add additives to the electrolyte. [3] Commonly used additives include: inorganic chloride ions, organic polyether compounds, sulfur-containing compounds and gelatin.

[0003] Graphene has unique properties such as high aspect ratio, large specific surface area (>2000m 2 g −1 )、Excellent thermal conductivity (3000-6000Wm −1 K −1 ), excellent strength and elastic modulus, and is considered to be an ideal reinforcing material for strengthening metal matrix composites [4] . Adding an appropriate amount of graphene oxide to the electrolyte can refine the grains, reduce the pores between the grains, improve the surface quality of the copper foil, and thus show better mechanical and electrical properties. Adding graphene oxide to the solution, the graphene is dispersed on the copper foil. Because of its high strength and toughness, the graphene particles distributed at the grain boundaries can effectively hinder the growth of grains and refine the grains. The formed Cu-OC interface has good interface bonding strength and can effectively transfer the load. [5] In addition, during the electrodeposition process, part of the graphene oxide is reduced and has good lubricity, which can effectively improve the wear resistance of the copper foil.

[0004] Due to the special layered structure of graphene, when too much graphene is added, it is easy to grow and agglomerate, which is not conducive to improving the mechanical properties and conductivity of copper foil. [6] In addition, the wettability between graphene and metal substrate is poor, and too much graphene content is not conducive to the electrodeposition process of copper foil. Therefore, as the content of graphene continues to increase, the performance of copper foil will first improve and then deteriorate. [7] Therefore, developing an electrolytic copper foil for lithium-ion batteries that can effectively incorporate graphene and thus exhibit excellent performance is a major research hotspot today.

[0005] References: [1] Yang Sen. Research on high performance ultra-thin electrolytic copper foil for lithium batteries[D]. Changzhou University, Jiangsu, 2022. [2] Zhang Xiaohong, Zhang Haijun, Zhang Jinlong. Lithium battery copper foil is on the rise[J]. China Nonferrous Metals, 2022, (03): 46-47. [3] Fan Binfeng, Wang Lina, Wang Qingfu, et al. Research on improving the high temperature elongation of lithium battery copper foil with new additives[J]. Electroplating & Finishing, 2024, 46(03): 108-113. [4] Cao J, Yang Q, Zhou L, et al., Microstructure, properties and synergetic effect of graphene oxide-functionalized carbon nanotubes hybridreinforced copper matrix composites prepared by DCelectrodeposition, Carbon212 (2023) 118157. [5] Bakshi SR, Lahiri D, Agarwal A. Carbonnanotube reinforced metalmatrix composites-a review[J]. Internationalmaterials reviews, 2010, 55(1):41-64. [6] McCoy TM, Turpin G, Teo BM, et al. Grapheneoxide: a surfactantor particle?[J]. Current opinion in colloid&interface science, 2019, 39: 98-109. [7] Fu Junfeng, Man Tiannan, Wang Jijie, et al. Effect of CNTs / MXene on the conductive properties of composite coatings[J]. Chemical Reaction Engineering and Technology, 2023, 39(06): 519-524. Summary of the invention

[0006] The object of the present invention is to overcome at least one disadvantage of the prior art and provide a graphene oxide modified additive for electrolytic copper foil.

[0007] The technical solution adopted by the present invention is: In the first aspect, the present invention provides a graphene oxide modified additive for electrolytic copper foil, wherein the added concentration of each component in the additive in the electrolyte is: graphene oxide 0.2-1.0 g / L, sodium polydisulfide dipropane sulfonate 15-20 mg / L, gelatin 1.0-2.5 g / L, hydrochloric acid 40-50 mg / L, methyl violet 10-18 mg / L, polyethylene glycol 4.5-8 mg / L, and hydroxyethyl cellulose 8-12 mg / L.

[0008] After the graphene of the present invention is oxidized, the graphene oxide still maintains the layered structure of graphite, but many oxygen functional groups are introduced on each layer of the graphene monolith. The introduction of oxygen-containing groups not only makes the graphene oxide chemically stable, but also provides surface modification active sites and a larger specific surface area for synthesizing graphene-based / graphene oxide-based materials.

[0009] In some examples, the mass addition ratio of graphene oxide and gelatin in the additive is (1.0-1.5): (5-7.5).

[0010] In some examples, the mass addition ratio of hydrochloric acid and methyl violet in the additive is 3:1.

[0011] In some examples, the mass addition ratio of sodium polydipropylene glycol disulfide to polyethylene glycol in the additive is 3:1.

[0012] In some examples, the concentration of each component in the additive is: graphene oxide 0.4 g / L, sodium polydisulfide bispropane sulfonate 18 mg / L, gelatin 2.0 g / L, hydrochloric acid 45 mg / L, methyl violet 15 mg / L, polyethylene glycol 6.0 mg / L, and hydroxyethyl cellulose 9 mg / L.

[0013] In a second aspect, the present invention provides a method for preparing a high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries, comprising the following steps: adding the additive described in the first aspect to a copper sulfate electrolyte and mixing, and sequentially performing electrolytic foil production, roughening treatment, curing treatment, passivation treatment, and anti-oxidation treatment to obtain the high-strength and ultra-thin electrolytic copper foil material.

[0014] In some examples, the plating solution composition of the smooth zinc plating process is: NiSO4·6H2O 39-41 g / L, ZnSO4·7H2O 19-21 g / L, CoSO4·7H2O 4-6 g / L.

[0015] In some examples, the high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries has a tensile strength greater than 500 MPa, an elongation greater than 4%, and a surface roughness less than 300 nm.

[0016] The beneficial effects of the present invention are: The high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries of the present invention has excellent mechanical properties, no obvious pinholes, and can significantly improve the roughness of the copper foil surface. The prepared copper foil material has a tensile strength greater than 500 MPa, an elongation greater than 4%, and a surface roughness less than 300 nm. The problem of poor mechanical properties of the copper foil is solved through the synergistic effect between specific components. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of the finished electrolytic copper foil obtained in Example 1.

[0018] Figure 2 The surface roughness diagrams of the finished electrolytic copper foils obtained in Examples 1, 3, 5 and 6 are shown respectively.

[0019] Figure 3 This is a SEM image of the finished electrolytic copper foil obtained in Comparative Example 3. DETAILED DESCRIPTION

[0020] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0021] The preparation method of the electrolytic copper foil material in each example of the present invention comprises the following steps: adding the configured additives of each example to a copper sulfate electrolyte and mixing, and sequentially performing electrolytic foil production, roughening treatment, curing treatment, a rough surface heat-resistant layer process, a smooth surface galvanized layer process, an anti-oxidation process, an impregnation treatment process and a drying process to obtain the high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0022] In some examples, the plating solution composition of the smooth zinc plating process is: NiSO4·6H2O 40 g / L, ZnSO4·7H2O 20 g / L, CoSO4·7H2O 5 g / L.

[0023] Example 1 The additive composition of this example is: graphene oxide 0.2g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 1.0g / L, hydrochloric acid 45mg / L, methyl violet 15mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0024] Example 2 The additive composition of this example is: graphene oxide 0.3g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 1.5g / L, hydrochloric acid 45mg / L, methyl violet 15mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0025] Example 3 The additive composition of this example is: graphene oxide 0.2g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 1.0g / L, hydrochloric acid 45mg / L, methyl violet 15mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0026] Example 4 The additive composition of this example is: graphene oxide 0.4g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 2.0 g / L, hydrochloric acid 45mg / L, methyl violet 15mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0027] Example 5 The additive composition of this example is: graphene oxide 0.4g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 2.0 g / L, hydrochloric acid 48mg / L, methyl violet 16mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0028] Example 6 The additive composition of this example is: 0.4g / L graphene oxide, 18mg / L sodium polydisulfide dipropane sulfonate, 2.0g / L gelatin, 45mg / L hydrochloric acid, 15mg / L methyl violet, 6.0mg / L polyethylene glycol, and 9mg / L hydroxyethyl cellulose. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0029] Example 7 The additive composition of this example is: graphene oxide 0.6g / L, sodium polydisulfide dipropane sulfonate 15mg / L, gelatin 1.9 g / L, hydrochloric acid 48mg / L, methyl violet 16mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0030] Example 8 The additive composition of this example is: graphene oxide 0.6g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 1.9 g / L, hydrochloric acid 42mg / L, methyl violet 14mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 10mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0031] Example 9 The additive composition of this example is: graphene oxide 0.6g / L, sodium polydisulfide dipropane sulfonate 15mg / L, gelatin 1.9 g / L, hydrochloric acid 42mg / L, methyl violet 14mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 12mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0032] Example 10 The additive composition of this example is: graphene oxide 0.6g / L, polydisulfide sodium dipropane sulfonate 19.5mg / L, gelatin 1.9 g / L, hydrochloric acid 42mg / L, methyl violet 14mg / L, polyethylene glycol 6.5mg / L, hydroxyethyl cellulose 12mg / L. The preparation process is through electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying treatment, to obtain the high-strength ultra-thin electrolytic copper foil material for lithium-ion batteries.

[0033] Comparative Example 1 The additive composition of this example is: 15 mg / L sodium polydisulfide dipropane sulfonate, 1.0 g / L gelatin, 45 mg / L hydrochloric acid, 15 mg / L methyl violet, 5.0 mg / L polyethylene glycol, and 8 mg / L hydroxyethyl cellulose. The preparation process includes electrolytic foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc coating process, anti-oxidation process, impregnation treatment process, and drying process.

[0034] Comparative Example 2 The additive composition of this example is: graphene oxide 0.2g / L, polydisulfide sodium dipropane sulfonate 15mg / L, gelatin 5.0g / L, hydrochloric acid 45mg / L, methyl violet 15mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 8mg / L. The preparation process includes electrolytic foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating process, anti-oxidation process, impregnation treatment process and drying process.

[0035] Comparative Example 3 The additive composition of this example is: graphene oxide 0.4g / L, polydisulfide sodium dipropane sulfonate 18mg / L, gelatin 2.0g / L, hydrochloric acid 45mg / L, methyl violet 15mg / L, polyethylene glycol 6.0mg / L, hydroxyethyl cellulose 1mg / L. The preparation process includes electrolytic foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc coating process, anti-oxidation process, impregnation treatment process and drying process.

[0036] Comparative Example 4 The additive composition of this example is: graphene oxide 0.6g / L, sodium polydisulfide dipropane sulfonate 15mg / L, gelatin 1.9 g / L, hydrochloric acid 70mg / L, methyl violet 14mg / L, polyethylene glycol 5.0mg / L, hydroxyethyl cellulose 10mg / L. The preparation process includes electrolytic foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc plating layer process, anti-oxidation process, impregnation treatment process and drying process.

[0037] Comparative Example 5 The additive composition of this example is: graphene oxide 0.6g / L, polydisulfide sodium dipropane sulfonate 19.5mg / L, gelatin 1.9 g / L, hydrochloric acid 42mg / L, methyl violet 14mg / L, polyethylene glycol 6.5mg / L, hydroxyethyl cellulose 12mg / L. The preparation process includes electrolytic foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc coating process, anti-oxidation process, impregnation treatment process and drying process.

[0038] Comparative Example 6 The additive composition of this example is: 0.4g / L ordinary graphene, 18mg / L sodium polydisulfide dipropane sulfonate, 2.0g / L gelatin, 45mg / L hydrochloric acid, 15mg / L methyl violet, 6.0mg / L polyethylene glycol, 9mg / L hydroxyethyl cellulose. The preparation process includes electrolytic raw foil, roughening treatment, curing treatment, rough surface heat-resistant layer process, smooth surface zinc coating process, anti-oxidation process, impregnation treatment process and drying process.

[0039] Performance Testing According to the national standard "GB / T 15970.7-2000" tensile test, the prepared electrolytic copper foil material was tested. The tensile strength, elongation and surface roughness of the high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries implemented above are shown in Table 1.

[0040] Table 1 Performance test results of different electrolytic copper foil materials

[0041] From the data in Table 1, we can see that: 1) Example 6 of the present invention, graphene oxide 0.4 g / L, sodium poly (disulfide bispropane sulfonate) 18 mg / L, gelatin 2.0 g / L, hydrochloric acid 45 mg / L, methyl violet 15 mg / L, polyethylene glycol 6.0 mg / L, hydroxyethyl cellulose 9 mg / L, has the best performance among all the examples.

[0042] 2) In Example 3 and Comparative Example 1, it can be seen that without adding graphene oxide, the tensile strength, elongation and surface roughness of the copper foil are deteriorated.

[0043] 3) In Comparative Example 4, it can be found that the additive exceeding the hydrochloric acid range causes the tensile strength, elongation and surface roughness of the copper foil to deteriorate.

[0044] 4) In Comparative Example 6, it can be found that the tensile strength, elongation and surface roughness of the copper foil obtained by adding ordinary graphene are inferior to those by adding graphene oxide.

[0045] 5) Figure 1 This is a SEM image of the finished electrolytic copper foil obtained in Example 1. Figure 1It can be seen that under the appropriate electrolyte additives, the surface grains of the copper foil are evenly distributed, there are no pinholes, and the surface is smooth and flat.

[0046] 6) Figure 2 The surface roughness diagram of the finished electrolytic copper foil obtained in Examples 1, 3, 5 and 6. It can be seen that the surface roughness of Example 5 is the lowest, indicating that the surface is smoother, which can significantly improve the tensile strength, elongation and surface roughness of the copper foil.

[0047] 7) Figure 3 This is a SEM image of the finished electrolytic copper foil obtained in Comparative Example 3. The hydroxyethyl cellulose content below the given range results in large voids on the surface of the copper foil, significantly reduces the tensile strength and elongation, and worsens the surface roughness.

[0048] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A graphene oxide modified additive for electrolytic copper foil, characterized in that: The added concentration of each component in the additive in the electrolyte is: graphene oxide 0.2-1.0 g / L, sodium polydisulfide dipropane sulfonate 15-20 mg / L, gelatin 1.0-2.5 g / L, hydrochloric acid 40-50 mg / L, methyl violet 10-18 mg / L, polyethylene glycol 4.5-8 mg / L, hydroxyethyl cellulose 8-12 mg / L.

2. The graphene oxide modified additive for electrolytic copper foil according to claim 1, characterized in that: The mass addition ratio of graphene oxide and gelatin in the additive is (1.0-1.5): (5-7.5).

3. The graphene oxide modified additive for electrolytic copper foil according to claim 1, characterized in that: The mass addition ratio of hydrochloric acid and methyl violet in the additive is 3:

1.

4. The graphene oxide modified additive for electrolytic copper foil according to claim 1, characterized in that: The mass addition ratio of sodium polydipropane disulfide sulfonate and polyethylene glycol in the additive is 3:

1.

5. The graphene oxide modifying additive for electrolytic copper foil according to any one of claims 1 to 4, characterized in that: The concentration of each component in the additive is: graphene oxide 0.4 g / L, sodium polydisulfide dipropane sulfonate 18 mg / L, gelatin 2.0 g / L, hydrochloric acid 45 mg / L, methyl violet 15 mg / L, polyethylene glycol 6.0 mg / L, and hydroxyethyl cellulose 9 mg / L.

6. A method for preparing a high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries, characterized in that: The method comprises the following steps: adding the additive described in any one of claims 1 to 5 into a copper sulfate electrolyte and mixing, and sequentially performing electrolytic foil production, roughening treatment, curing treatment, passivation treatment, and anti-oxidation treatment to obtain the high-strength ultra-thin electrolytic copper foil material.

7. The preparation method according to claim 6, characterized in that: The plating solution composition of the smooth zinc plating process is: NiSO4·6H2O 39-41 g / L, ZnSO4·7H2O 19-21 g / L, CoSO4·7H2O 4-6 g / L.

8. The preparation method according to claim 6, characterized in that: The high-strength and ultra-thin electrolytic copper foil material for lithium-ion batteries has a tensile strength greater than 500 MPa, an elongation greater than 4%, and a surface roughness less than 300 nm.